NMR mapping of the recombinant mouse major urinary protein I binding site occupied by the pheromone 2-sec-butyl-4,5-dihydrothiazole - Zídek, L; Stone, M J; Lato, S M; Pagel, M D; Miao, Z; Ellington, A D; Novotny, M V (Biochemistry (Easton), 1999)
The interactions between the mouse major urinary protein isoform MUP-I and the pheromone 2-sec-butyl-4,5-dihydrothiazole have been characterized in solution. (15)N-labeled and (15)N, (13)C-doubly-labeled recombinant MUP-I were produced in a bacterial expression system and purified to homogeneity. Racemic 2-sec-butyl-4, 5-dihydrothiazole was produced synthetically. An equilibrium diffusion assay and NMR titration revealed that both enantiomers of the pheromone bind to the recombinant protein with a stoichiometry of 1 equiv of protein to 1 equiv of racemic pheromone. A micromolar dissociation constant and slow-exchange regime dissociation kinetics were determined for the pheromone-protein complex. (1)H, (15)N, and (13)C chemical shifts of MUP-I were assigned using triple resonance and (15)N-correlated 3D NMR experiments. Changes in protein (1)H(N) and (15)N(H) chemical shifts upon addition of pheromone were used to identify the ligand binding site. Several amide signals, corresponding to residues on one side of the binding site, were split into two peaks in the saturated protein-ligand complex. Similarly, two overlapping ligand spin systems were present in isotope-filtered NMR spectra of labeled protein bound to unlabeled pheromone. The two sets of peaks were attributed to the two possible chiralities of the pheromone. Intermolecular NOEs indicated that the orientation of the pheromone in the MUP-I binding cavity is opposite to that modeled in a previous X-ray structure.